2013
DOI: 10.1155/2013/758731
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Vocal Tract Characteristics for Acoustic Discrimination of Pathological Voices

Abstract: This paper investigates the effectiveness of measures related to vocal tract characteristics in classifying normal and pathological speech. Unlike conventional approaches that mainly focus on features related to the vocal source, vocal tract characteristics are examined to determine if interaction effects between vocal folds and the vocal tract can be used to detect pathological speech. Especially, this paper examines features related to formant frequencies to see if vocal tract characteristics are affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
5
26
0
Order By: Relevance
“…Variability in these structural components explains the disparities in acoustic features among speakers. Strong correlation has been shown to exist between vocal tract morphology and vocal characteristics in both dysphonic 1 and nondysphonic subjects. 1,2 Jesus et al 3 reported higher values for the second formant (second preferred harmonic) in patients with unilateral vocal fold paralysis, in comparison to controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability in these structural components explains the disparities in acoustic features among speakers. Strong correlation has been shown to exist between vocal tract morphology and vocal characteristics in both dysphonic 1 and nondysphonic subjects. 1,2 Jesus et al 3 reported higher values for the second formant (second preferred harmonic) in patients with unilateral vocal fold paralysis, in comparison to controls.…”
Section: Introductionmentioning
confidence: 99%
“…Strong correlation has been shown to exist between vocal tract morphology and vocal characteristics in both dysphonic 1 and nondysphonic subjects. 1,2 Jesus et al 3 reported higher values for the second formant (second preferred harmonic) in patients with unilateral vocal fold paralysis, in comparison to controls. Similarly, Titze 2 described clustering of the first two formants in patients with unilateral vocal fold paralysis, alluding to the narrowing of the vocal tract in compensation for inefficient phonation.…”
Section: Introductionmentioning
confidence: 99%
“…To simulate burst packet loss conditions, the burstiness of the packet losses was set to 0.99, where the mean and maximum consecutive packet losses were measured as 1.9 and 5.6 frames, respectively. First, the log spectral distortion (LSD) [25] was measured between the original and decoded signal. It is defined as…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Speech pathology detection studies in literature involve working on various databases. Few studies use private databases collected in local hospitals [9][12] [13] [14], with one or multiple pathologies. Massachusetts Eye and Ear Infirmary (MEEI) dataset commercialized by KayPENTAX is used widely in the literature [5] [15].…”
Section: Literature Studymentioning
confidence: 99%